Democratic Like Us? Political Orientation and the Effect of Making Democracy Salient on Anti-Israel Attitude. Issue 1 (28th October 2015) - Lelkes, Yphtach; Malka, Ariel; Sheets, Penelope
Abstract: Israel is viewed unfavorably among wide segments of the public within several European democracies, despite being regarded itself as a Western democracy. Does drawing attention to Israel's democratic attributes improve views toward Israel? In two surveys with Dutch national samples, anti-Semitic affect, low anti-Arab/Muslim affect, and left-wing political orientation independently predicted anti-Israel sentiment. However, in experiments embedded within the surveys, making salient Israel's democratic attributes had opposite effects on Israel attitude across those on the right and the left – slightly decreasing anti-Israel sentiment among those with a right-wing orientation but slightly increasing anti-Israel sentiment among those with a left-wing orientation. We discuss potential explanations grounded in social psychological theory as well as implications for the strategic communication efforts of groups seeking to influence attitudes toward Israel.